Global Stability of HIV-1 Infection Model with Two Time Delays - Hui Miao; Xamxinur Abdurahman; Ahmadjan Muhammadhaji (Abstract and Applied Analysis)
We investigate global dynamics for a system of delay differential equations which describes a virus-immune interaction in vivo. The model has two time delays describing time needed for infection of cell and CTLs generation. Our model admits three possible equilibria: infection-free equilibrium, CTL-absent infection equilibrium, and CTL-present infection equilibrium. The effect of time delay on stability of the equilibria of the CTL immune response model has been studied.